Delivery of Non-Academic Student Support Services by Staff at Kyambogo University - Nakimuli, Agnes (East African Journal of Education Studies, 2023)
Non-academic student support services significantly contribute to supporting and enhancing students’ academic, social and welfare experiences, thereby supporting their subsequent success in higher education. Students’ activities at the university go beyond the lecture room setting since they spend 70% of their time out of the lecture room. Hence, higher education institutions should promote what happens outside of the lecture room in order to enhance positive behavior amongst students, which will contribute to responsible citizenship in the nation. Staff in student affairs departments are key in assisting students in their experiences outside the classroom. However, as a result of changes in higher education, the roles of these staff have become broad, complex, non-specific, dynamic, and comprehensive yet there is declining funding and staffing. Hence, an understanding of how they deliver the services is vital to the effectiveness of the institution. Higher education institutions endeavor to provide the services, but the ways the services are delivered continue to be overlooked and hence not well understood. This study presents one of the latest findings of a recent study done in Uganda on the delivery of non-academic student support services by staff at Kyambogo University. The study aimed at exploring how the staff deliver non-academic student support services at Kyambogo University. It employed a qualitative approach that involved 11 staff purposively selected from the units that deliver non-academic student support services. The findings revealed three key aspects in the delivery of the services by staff; policy guidelines, management roles and capacity building. The staff made use of both internal and external policies and guidelines and carried out training for both staff and students. This study also revealed that the effective delivery of the services was hindered by inadequate funding, which affects other services like staffing and facilities. Staff revealed that in order to navigate the challenges, they worked with other departments in the university and student leaders. I therefore, recommend that the management of Kyambogo University ensures that the delivery of the services is clearly understood by all stakeholders; this will help in its improvement. Further, policies should not only be formulated but also be well implemented, and find alternative sources of funding like engaging in public-private partnerships and outsourcing services like halls of residence in order to improve funding in the university. In addition, it is essential that staff receive adequate training and support to effectively deliver non-academic student support services